Lopinavir/ritonavir monotherapy after virologic failure of first-line antiretroviral therapy in resource-limited settings - Bartlett J. (2017)
Objective: To evaluate virologic response rates of lopinavir/ritonavir (LPV/r) monotherapy as second-line antiretroviral treatment (ART) among adults in resource-limited settings (RLSs). Design: An open-label pilot study of LPV/r monotherapy in participants on first-line nonnucleoside reverse transcriptase inhibitor three-drug combination ART with plasma HIV-1 RNA 1000-200 000 copies/ml. Methods: Participants were recruited from five sites in Africa and Asia within the AIDS Clinical Trials Group (ACTG) network. All participants received LPV/r 400/100 mg twice daily. The primary endpoint was remaining on LPV/r monotherapy without virologic failure at week 24. Participants with virologic failure were offered addition of emtricitabine and tenofovir (FTC/TDF) to LPV/r. Results: Mutations associated with drug resistance were encountered in nearly all individuals screened for the study. One hundred and twenty-three participants were enrolled, and 122 completed 24 weeks on study. A high proportion remained on LPV/r monotherapy without virologic failure at 24 weeks (87%). Archived samples with HIV-1 RNA levels less than 400 copies/ml at week 24 (n = 102) underwent ultrasensitive assay. Of these individuals, 62 had levels less than 40 copies/ml and 30 had levels 40-200 copies/ml. Fifteen individuals experienced virologic failure, among whom 11 had resistance assessed and two had emergent protease inhibitor mutations. Thirteen individuals with virologic failure added FTC/TDF and one individual added FTC/TDF without virologic failure. At study week 48, 11 of 14 adding FTC/TDF had HIV-1 RNA levels less than 400 copies/ml. Conclusion: In this pilot study conducted in diverse RLS, LPV/r monotherapy as second-line ART demonstrated promising activity. © 2012 Wolters Kluwer Health | Lippincott Williams & Wilkins.